(untitled) (Comunicação & Inovação, 2017)
Based on a bibliographical research, this article aims to discuss public interest and freedom of the press as preconditions for the development of society and affirmation of democracy. Journalism is a social profession, and public interest guides the journalist. However, several restrictions may threat journalism. In such perspective, these issues are analyzed according to authors that address the profession of the journalist and authors who study the legal sciences and consider journalism and public interest as unquestionable values in the process of social evolution.